Time and charge calibration of the LHAASO electromagnetic particle detectors - Pang B. (2023)
The one square kilometer array (KM2A), a sub-array of Large High Altitude Air Shower Observatory (LHAASO) experiment, consists of 5195 electromagnetic particle detectors (EDs) and 1188 muon detectors (MDs), has been built over three-quarters scale. Its main scientific goal is to search gamma-ray sources at energies above 100 TeV. Offline calibration method has been used to calibrate thousands of EDs to guarantee the key performances of the array such as angular resolution and pointing accuracy within 0.1° during long-term operation. The experimental results of the 3/4 array show that this method can be used to determine the detector time offset with an accuracy of 0.5 ns and the particle number density with an accuracy of a few percent. Furthermore, we monitor the calibration parameters during the array operation and update the calibration results regularly to ensure the data quality of the detector.